The Arrest of the Wanted Defendant as an Alternative to Detention (in the Absence of the Defendant) in the Criminal Proceedings - Marabyan, S. (Bulletin of Yerevan University C: Jurisprudence, 2019)
Within the scope of this article, the author has raised the issues of imposing detention as a preventive measure without the involvement of the defendant in the proceedings and concluded that without the defendant’s participation, the hearings on the detention may be considered legitimate only when the international reconnaissance has been declared. In this respect, the author agrees with the legal positions of the Court of Cassation, but he believes that its scope should be limited, as it often causes abuses and arbitrariness. The author thinks that, in the case of domestic reconnaissance, arrest but not detention may be imposed on a person. This will not only exclude the practice of arbitrary and artificial declaration of reconnaissance, but also the doubling of the courts’ workload.